Unmet needs in the depressed primary care elderly and their relation to severity of depression: results from the AgeMooDe study - Alltag, Sophie; Weyerer, Siegfried (Aging & mental health, 2017)
OBJECTIVES: This study aims at examining the distribution of unmet environmental, physical, social and psychological care needs in a sample of the oldest old primary care patients with different levels of depression severity. Furthermore, the objective of this study was to analyze the association between specific unmet care needs and severity of depression. METHOD: The sample of patients aged 75 years (n = 202) and more was derived from the multicenter prospective cohort study AgeMooDe ('Late-life depression in primary care: Needs, health care utilization and costs'). Patients were assessed via structured clinical interviews containing the German version of the Camberwell Assessment of Need for the Elderly (CANE) and the German Hospital Anxiety and Depression Scale (HADS-D). Descriptive statistics, Spearman correlation coefficients and binary logistic regression analyses were computed. RESULTS: Unmet needs appeared to be substantially higher in the patient group with higher levels of depression severity according to the HADS-D score. Overall, there was weak positive linear correlation between depression and CANE total unmet needs. Except of the physical unmet needs category, all other CANE care categories showed little to moderate positive linear correlations with depression according to the HADS-D score. Depression and psychological unmet needs showed the strongest of all correlations, followed by social unmet needs. The binary logistic regression analysis revealed that patients having psychological unmet needs were 4.8 times more likely diagnosed with a probable depression. CONCLUSION: Systematic needs assessment, especially psychological needs, may play a crucial role in the course of prevention and effective treatment of late-life depression in the primary care context.